Ecotoxicological studies on giant clam (Tridacnidae) environmental problems and future concerns. - Blidberg, Eva (Stockholm, Sweden Department of Systems Ecology, 2004)
Doctoral thesis in marine ecotoxicology
Keywords: Giant clam fisheries; Giant clam culture